A simple route to synthesize nickel ferrite (NiFe2O4) nanoparticles using egg white - Maensiri, Santi; Masingboon, Chivalrat; Boonchom, Banjong; Seraphin, Supapan (My University, 2007)
NiFe2O4 nanoparticles were synthesized by a simple and cost-effective method using Ni and Fe nitrates and freshly extracted egg white (ovalbumin) in an aqueous medium. The X-ray diffraction and selected-area electron diffraction results indicated that the synthesized nanoparticles have only the inverse spinel structure without the presence of any other phase impurities. Room temperature magnetization results showed a ferromagnetic behavior of the NiFe2O4 nanoparticles, with saturation-specific magnetization values in the range of 26.4-42.5 emu/g at 10 kOe. © 2006 Acta Materialia Inc.
Keywords: Electron microscopy; Magnetic properties; Nanoparticles; Nickel ferrite; Synthesis